Work orientations and economics - Milena Nikolova (Global Labor Organization (GLO), 2025)
A growing body of research in economics shows that workers care about more than just pay, often seeking social status, career mobility, or meaningful work. This chapter introduces the work orientations framework - a concept from psychology - as a unifying lens for understanding these motivations. Work orientations capture individuals' core beliefs about the role of work: earning a living ("paycheck"), achieving recognition and advancement ("career"), or finding fulfillment ("calling"). These orientations are not mutually exclusive, and many people hold a mix that shapes their workplace behavior. Economists have long examined financial incentives, alignment with an organization's mission, and career ambitions, but these strands remain fragmented. Integrating them within the work orientations framework broadens standard economic models, offers a richer view of labor supply and effort, and suggests new priorities for data collection, measurement, and theory development. The chapter reviews current evidence and outlines avenues for future empirical and conceptual research.
Keywords: J22; J24; J28; I31; 330; Work orientations; Job orientation; Career orientation; Calling orientation; Labor economics